Evaluasi Kualitas Layanan Website Dinas Pariwisata Kabupaten Banyuwangi Dengan Metode e-Govqual, Human Organization Technology (HOT) Fit dan Kano Model - Elmanda Krisna Jaya; Admaja Dwi Herlambang; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
This study aims to determine the service quality of the DISBUDPAR Banyuwangi site using the e-Govqual method which functions to measure the quality of e-government services consisting of the ease of users (human) as end users, using Human Organization Technology (HOT) -Fit adding Organization features in replacement service quality and two-way relationship (reciprocity) between the organization and net benefits (net benefits) obtained from the system, and the use of the Kano Model method used to obtain the level of user satisfaction (end users). This study collected data with a questionnaire as a research instrument. The research questionnaire consisted of 188 questions with a sample of 100 respondents. The results of the study concluded that the e-Govqual method was in the high category (80.57%), Human Organization Technology (HOT) -Suitable in the high category (81.57%) and the Kano Model was also included in the High category (80.95%). The results of this study will provide a discussion on each method and choose variables that have indicator values based on the average (average). The e-Govqual method needs to improve the indicator section on the Ease of Use, Trust and Content and Information Appearance variables. Human Organizational Technology Method (HOT) Suitable to improve the indicator part of the Human Factor and Technology variables and the Kano Model method needs to improve the indicator section on Function variables and Route Planning, Visual Design and Content and Member Information Management.